Identification and characterization of serovar-independent immunogens in Actinobacillus pleuropneumoniae - Antenucci,F; Fougeroux,C; Bosse,JT; Magnowska,Z; Roesch,C; Langford,P; Holst,PJ; Bojesen,AM (Veterinary Research, 2017)
Despite numerous actions to prevent disease, Actinobacillus pleuropneumoniae (A. pleuropneumoniae) remains a majorcause of porcine pleuropneumonia, resulting in economic losses to the swine industry worldwide. In this paper, wedescribe the utilization of a reverse vaccinology approach for the selection and in vitro testing of serovar-independentA. pleuropneumoniae immunogens. Potential immunogens were identifed in the complete genomes of three A. pleuropneumoniaestrains belonging to diferent serovars using the following parameters: predicted outer-membrane subcellularlocalization; ≤ 1 trans-membrane helices; presence of a signal peptide in the protein sequence; presence in allknown A. pleuropneumoniae genomes; homology with other well characterized factors with relevant data regardingimmunogenicity/protective potential. Using this approach, we selected the proteins ApfA and VacJ to be expressedand further characterized, both in silico and in vitro. Additionally, we analysed outer membrane vesicles (OMVs) of A.pleuropneumoniae MIDG2331 as potential immunogens, and compared deletions in degS and nlpI for increasing yieldsof OMVs compared to the parental strain. Our results indicated that ApfA and VacJ are highly conserved proteins, naturallyexpressed during infection by all A. pleuropneumoniae serovars tested. Furthermore, OMVs, ApfA and VacJ wereshown to possess a high immunogenic potential in vitro. These fndings favour the immunogen selection protocolused, and suggest that OMVs, along with ApfA and VacJ, could represent efective immunogens for the prevention ofA. pleuropneumoniae infections in a serovar-independent manner. This hypothesis is nonetheless predictive in nature,and in vivo testing in a relevant animal model will be necessary to verify its validity.